I'm not sure how to tackle this problem: If the nth partial sum of a series a(n) from 1 to infinity is s(n)=3-n(2)^(-n), find a(n) and the sum of a(n) from n=1 to infinity. Thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by pianopiano I'm not sure how to tackle this problem: If the nth partial sum of a series a(n) from 1 to infinity is s(n)=3-n(2)^(-n), find a(n) and the sum of a(n) from n=1 to infinity. Thanks So right? Well hint for part one: Note that Hint for part two:
View Tag Cloud